The Academic Librarian as the Subaltern: An Institutional Ethnography of a Feminized Profession - Revitt, Eva Justyna (University of Alberta, 2020)
I locate this study within the context of my own work and experiences as an academic librarian and the disconnect that I have often felt between what I consider my role and the value of my work to be versus the perception and understanding of that role, the work, and its value by others. Overwhelmingly, librarians working at Canadian universities are considered academic staff, if not faculty. However, the role and fit of the academic librarian within the academic enterprise is overshadowed and frequently misunderstood. As the subaltern, librarians’ expertise and contribution to the university’s academic mission is often sidelined: the nature of the work too frequently viewed through an organizational rather than an academic lens and characterized as preoccupied with a structured set of regularized responsibilities. The goal of this study is to make visible the processes that shape the work experiences of academic librarians such as they are. Two research questions served as the impetus for this study: How is it that the academic librarian’s lesser status is the ideal at Canadian universities? What are the social processes that shape this ideal? This study is informed by the epistemological, ontological, and methodological assumptions of institutional ethnography: a research approach developed by the Canadian social theorist and sociologist, Dorothy Smith. Institutional ethnography considers the everyday, lived experiences of people as the research problematic—a term used by Smith to focus the inquiry on the actual, social, and active world as it is lived and experienced by people. An institutional ethnography progresses through layers, in this case the progression is from the academic librarian, to the library, to the institution, and beyond, to reveal how power structures external to the local setting influence daily life. To understand how the everyday world is put together so that things happen as they do, the focus of the investigation is on individual experiences and what people are doing relationally. However, in institutional ethnography the actions and experiences of people within a particular setting are not regarded as representative. Rather, the local experience is regarded as a window into the role of power. It is a politically charged and activist type of scholarship. Because institutional ethnography is concerned with explicating the actual rather than formulating or advancing the theoretical, the emphasis is on discovery rather than hypothesis testing. The findings of this study reveal how the value of librarians’ work is socially constructed and based on work that is perceived as women’s work; how the work of librarians is organized as library work rather than academic work; how accreditation bodies and the professions privilege the library over the librarian; and how institutional policies and practices position the librarian as academic on the margins of the academy. These social processes reveal how things come about so that librarians’ experiences as academic staff are such as they are. However, it is ideologies that help us understand why things are the way they are. I propose that two ideological codes—women’s work and the library—permeate our social consciousness, including speech, text, and talk, and infuse librarians’ work with particularizing characteristics. Ultimately, the findings of this study tie librarians’ work experiences to the necessary and gendered exploitation of labour that happens within a capitalist mode of production.